Educational Vouchers: Freedom to Choose? - Jordan Reel; Walter E. Block (Contemporary Economics, 2013)
Milton Friedman is famous for his book title: 'Free to Choose.' He also favors educational vouchers, which denies the freedom to choose to people who do not wish to subsidize the education of other people's children. Thus, he is guilty of a logical contradiction. Why is it important to assess whether Friedman's views on educational vouchers are logically consistent with his widespread reputation as an advocate of free enterprise, and, thus, freedom to chose? It is important to assess all figures in political economy, and indeed all of scholarship, for logical consistency. It is particularly important to do so in the present case, given the prestige in certain quarters accorded to this Nobel prize-winning economist. We argue in this paper that Friedman's reputation for logical consistency, and adherence to the philosophy of laissez faire capitalism, are both overblown. Our solution to this challenge is to completely privatize education. Friedman does not advocate that vouchers be utilized for food, clothing or shelter; we see no relevant difference in the case of education. What is the justification of the undertaken topic? This topic is important because education of the next generation is crucial for the upkeep and improvement of society. What is the aim of the present study? It is to demonstrate that the solution offered by M. Friedman and R. Friedman (1990) is highly problematic. What is the methodology used in the study? We quote from this author, and criticize his analysis. What are our main results and conclusions/recommendations? We conclude that the last best hope for the educational industry is laissez faire capitalism, not the mixed economy recommended by Friedman.
Keywords: I2; I28; 330; economic freedom; choice; school vouchers; Milton Friedman